2010
DOI: 10.1037/a0021370
|View full text |Cite
|
Sign up to set email alerts
|

Communalism, familism, and filial piety: Are they birds of a collectivist feather?

Abstract: The present studies examined the extent to which (a) communalism, familism, and filial piety would pattern onto a single family/relationship primacy construct; (b) this construct would be closely related to indices of collectivism; and (c) this construct would be related to positive psychosocial functioning and psychological distress. In Study 1, 1,773 students from nine colleges and universities around the United States completed measures of communalism, familism, and filial piety, as well as of individualist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
209
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(221 citation statements)
references
References 99 publications
10
209
1
1
Order By: Relevance
“…However, when Schwartz et al (2010) administered the Steidel and Contreras (2003) Attitudinal Familism scale to diverse university samples across the United States, they found familism to be comprised of one overall factor that encompassed all the conceptually distinct subcomponents. Further, they found that familism and two related measures, communalism and filial piety, that respectively reflect family primacy in African and Asian cultures, clustered into a single latent factor.…”
Section: Family Relationships and Familism: Human Universals And Cultmentioning
confidence: 99%
“…However, when Schwartz et al (2010) administered the Steidel and Contreras (2003) Attitudinal Familism scale to diverse university samples across the United States, they found familism to be comprised of one overall factor that encompassed all the conceptually distinct subcomponents. Further, they found that familism and two related measures, communalism and filial piety, that respectively reflect family primacy in African and Asian cultures, clustered into a single latent factor.…”
Section: Family Relationships and Familism: Human Universals And Cultmentioning
confidence: 99%
“…The type of collectivism observed in China, for example, is markedly different from the types of collectivism observed in Mexico, India, and Iran. On this point, Schwartz et al (2010) discussed variations in collectivism across different cultural groups. For example, communalism (emphasis on social ties over individual achievements) is known to be an important value orientation among individuals of African descent.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of family and parental variables to adolescents' value acquisition has been a subject of interest for the scientific community (Bengtson et al 2002;Friedlmeier and Friedlmeier 2012;Grusec et al 2000;Pinquart and Silbereisen 2004;Schwartz et al 2010). A large body of studies points to family relational climate and parenting practices as operative mechanisms in the formation of children's values and the familial transmission of values (Bengtson et al 2002;Grusec 2002;Pinquart and Silbereisen 2004;Roberts et al 1999;Roest et al 2009a;White and Matawie 2004;Yi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of studies notes that beyond a family system's protective function, CV also have protective functions for individuals, such as promoting self-esteem and well-being (Ghazarian et al 2008), and protecting against anxiety and depression and distress (Zhang et al 2007). Schwartz et al (2010) hypothesized that CV facilitate the development of supportive relationships and a greater connectivity to social systems (e.g., family) and encourage persons to be responsible for their behavior and its consequences on others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation